Impact of Electrical Current on Single GaAs Nanowire Structure. Issue 8 (29th May 2021) - Bahrami, Danial; AlHassan, Ali; Davtyan, Arman; Zhe, Ren; Anjum, Taseer; Herranz, Jesús; Geelhaar, Lutz; Novikov, Dmitri V.; Timm, Rainer; Pietsch, Ullrich
Abstract : The impact of electrical current on the structure of single free‐standing Be‐doped GaAs nanowires grown on a Si 111 substrate is investigated. Single nanowires have been structurally analyzed by X‐ray nanodiffraction using synchrotron radiation before and after the application of an electrical current. The conductivity measurements on single nanowires in their as‐grown geometry have been realized via W‐probes installed inside a dual‐beam focused ion beam/scanning electron microscopy chamber. Comparing reciprocal space maps of the 111 Bragg reflection, extracted perpendicular to the nanowire growth axis before and after the conductivity measurement, the structural impact of the electrical current is evidenced, including deformation of the hexagonal nanowire cross section, tilting, and bending with respect to the substrate normal. For electrical current densities below 30 A mm −2, the induced changes in the reciprocal space maps are negligible. However, for a current density of 347 A mm −2, the diffraction pattern is completely distorted. The mean cross section of the illuminated nanowire volume is reconstructed from the reciprocal space maps before and after the application of electrical current. Interestingly, the elongation of two pairs of opposing side facets accompanied by shrinkage of the third pair of facets is found. The variations in the nanowire diameter, as well as their tilt and bending, are confirmed by scanning electron microscopy. To explain these findings, material melting due to Joule heating during voltage/current application accompanied by anisotropic deformations induced by the W‐probe is suggested. Abstract : Single GaAs nanowires grown on Si 111 have been structurally analyzed by X‐ray nanodiffraction before and after the application of an electrical current via W‐probe of a focused ion beam (FIB). After the conductivity measurement, a major deformation of the hexagonal nanowire cross section increasing with the applied current density is detected. These findings are explained by Joule heating accompanied by anisotropic deformations.